APAKAH MAHASISWA SUDAH MELEK KEUANGAN? - Maria Rio Rita; Benaya Chrisma Adiputra Pesudo (Dinamika Akuntansi Keuangan dan Perbankan, 2014)
Financial literacy is one of the needs for everyone in order to manage their personal finance.Person's ability to read, analyze, manage financial condition in making financial decisions can be made ​​to avoid financial problems. This study aims to determine whether factors such as gender, faculty, and grade point average (GPA) effect on student financial literacy. This research surveys 333 college students of Economics and Business Faculty also Science and Mathematics Faculty of Satya Wacana Christian University (UKSW) to examine their personal financial literacy based on gender, faculty and Grade Point Average (GPA).Binary logistic used to analyze the data.Results of this study indicate that financial literacy is influenced by faculty, whereas gender and GPA does not affect financial literacy. This study is expected to support the science of personal finance is still relatively rare compared to research in the field of corporate finance and capital markets.. Keywords: Financial Literacy, Gender, Faculty, Grade Point Average (GPA)